Bonding properties of Acacia mangium for Cross-Laminated Timber (CLT) manufacture - Mohd Zaili, Asnawi Nazran (2018)
This study aim is to evaluate bonding properties of Acacia mangium wood for lamination process. Shear performance of the laminated panel were evaluate for suitability of two different adhesives, phenol-resorcinol formaldehyde (PRF) and one-component polyurethane (PUR). Delamination tests were performing on samples that were subjected to accelerated aging to assess the durability of bonds in severe environmental conditions. Both tested adhesives produced boards with shear strength values within the edge bonding requirements of prEN 16351 for all manufacturing pressures. The PRF bonded specimens demonstrated superior durability characteristics in the delamination tests, while the PUR bonded specimens had the highest shear strength.